Ґрунтообробна техніка: наукові погляди на історію її розвитку - Мудрук, О.С. (Питання історії науки і техніки, 2009)
Сформулирован синтезирующий принцип теории исторического развития техники для обработки почвы. Приводятся постулаты этой теории. Рассматриваются идеализированная модель почвообрабатывающего орудия, схема и периоды его исторического развития. A synthetic principle of theory of historical development of tools for soil cultivation has been formulated. Postulates of this theory have been given. An idealised model of a soil cultivation tool, scheme and periods of its historical development have been considered.